Konsep Keadilan Sosial Dalam Bingkai Sila Kelima Pancasila (The Concept Of Social Justice Within The Fifth Principle Framework Of Pancasila) - Yunie Herawati (Jurnal Paradigma, 2014)
Our State To Consider Most Important The Social Justice. That Represent The Declaration Of Independence. Social Justice Is For All Indonesian People. The Important Social Justice Is Re Ected At Implementation Of State Government Exertion, At Section 9 Of 1945 Constitution, Specifying Obligation Execute The Principle Of State Government Which “Genuinely Fair”. Though Practically, To Realize In The Section 34 Article 2 Fourth Amandemen From 1945 Constitution, That “State Develop The System Of Guarantee Social For All People And Powered Of Weak Society And Unable To As According To Human Prestige”, Not Yet Can Be Executed Perfectly. Hence Returning At Fth Principle Of Pancasila Which Writer Make The Article Title, Inspire The Mind Grow Several Questions. Where Is Spirit Of That Go ? Where Social Justice Meant ? Dif Cult To Really Apply The Justice Which That As Fair As May Be ? Presumably To Behold And Comprehend To Return What And How Concept Of Social Justice According To Pancasila.